Kepemimpinan Transformasional Di Era Post Modern - Wasis Suseno (JURNAL LUXNOS, 2019)
Abstract: The modern Post era we are currently facing has the character of: attacking the special, universal, total, and absolute status of truth as understood in modernism. Single and universal truths are not recognized. There are only true truths for every society or community. Then truth is understood as fragmented into equal truths without a single normative accout beyond it. There is no tradition or ideology that stands on other traditions or other ideologies. What one believes to be true is no longer a single truth but part of truth pluralism. Therefor a leader understands the leadership of transformation in the post moderent era, apostle Paul explains, there are three levels of Transformational in the life of Believers, namely: 1) Position Transformation; 2) Behavior Transformation; 3) Community Transformation. If we can describe, the leadership of transformation in post-modern era, must have three real roles in leadership, 1. Spiritual Formation, 2. Theological Proficiency, 3. Practical & Ministry Proficieny. These three skills will be discussed in this paper. Abstrak: Era Pos modern yang kita hadapi saat ini bersifat: menyerang status kebenaran yang khusus, universal, total, dan absolut sebagaimana dipahami dalam modernisme. Kebenaran tunggal dan universal tidak diakui. Hanya ada kebenaran sejati untuk setiap masyarakat atau komunitas. Kemudian kebenaran dipahami sebagai terfragmentasi menjadi kebenaran yang setara tanpa satu pernyataan normatif di luarnya. Tidak ada tradisi atau ideologi yang berdiri di atas tradisi atau ideologi lain. Apa yang diyakini sebagai kebenaran bukan lagi kebenaran tunggal melainkan bagian dari pluralisme kebenaran. Untuk itu seorang pemimpin memahami transformasi kepemimpinan di era post moderent, Rasul Paulus menjelaskan, ada tiga tingkatan Transformasi dalam kehidupan Orang Beriman, yaitu: 1) Transformasi Jabatan; 2) Transformasi Perilaku; 3) Transformasi Komunitas. Jika bisa kita gambarkan, kepemimpinan transformasi di era postmodern, harus memiliki tiga peran nyata dalam kepemimpinan, 1. Formasi Spiritual, 2. Kecakapan Teologis, 3. Practical & Ministry Proficieny. Ketiga keterampilan tersebut akan dibahas dalam makalah ini.